Randomised crossover trial of rate feedback and force during chest compressions for paediatric cardiopulmonary resuscitation. Issue 5 (24th October 2016) - Gregson, Rachael Kathleen; Cole, Tim James; Skellett, Sophie; Bagkeris, Emmanouil; Welsby, Denise; Peters, Mark John
Abstract : Objective: To determine the effect of visual feedback on rate of chest compressions, secondarily relating the forces used. Design: Randomised crossover trial. Setting: Tertiary teaching hospital. Subjects: Fifty trained hospital staff. Interventions: A thin sensor-mat placed over the manikin's chest measured rate and force. Rescuers applied compressions to the same paediatric manikin for two sessions. During one session they received visual feedback comparing their real-time rate with published guidelines. Outcome measures: Primary: compression rate. Secondary: compression and residual forces. Results: Rate of chest compressions (compressions per minute (compressions per minute; cpm)) varied widely (mean (SD) 111 (13), range 89–168), with a fourfold difference in variation during session 1 between those receiving and not receiving feedback (108 (5) vs 120 (20)). The interaction of session by feedback order was highly significant, indicating that this difference in mean rate between sessions was 14 cpm less (95% CI −22 to −5, p=0.002) in those given feedback first compared with those given it second. Compression force (N) varied widely (mean (SD) 306 (94); range 142–769). Those receiving feedback second (as opposed to first) used significantly lower force (adjusted mean difference −80 (95% CI −128 to −32), p=0.002). Mean residual force (18 N, SD 12, range 0–49) was unaffected by the intervention. Conclusions: While visual feedback restricted excessive compression rates to within the prescribed range, applied force remained widely variable. The forces required may differ with growth, but such variation treating one manikin is alarming. Feedback technologies additionally measuring force (effort) could help to standardise and define effective treatments throughout childhood.